Analysis of Oil Price Oscillations, Exchange Rate Dynamics and Economic Performance - Manasseh, Charles O.; Ogbuabor, Janathan E.; Abada, Felicia C.; Okoro, Okoro E.U.; Egele, Aja Ebeke; Onwumere, Josaphat U. (International Journal of Energy Economics and Policy, 2018)
This study examined the influence of oil price oscillation and exchange rate dynamics on economic performance. While multiple regression models was adopted to examine the effect of oil price and exchange rate dynamics on economic performance, we employed Exponential Generalized Autoregressive Conditional Heteroschedasticity (EGARCH) to investigate the effect of oil price oscillation on exchange rate dynamic using annual time series data that covers the period 1970 to 2013. However, the results of the study suggested that real exchange rate exhibits volatility of about 16%. The result also shows that 10% increase in oil price leads to 19% increase in real exchange rate in the long run. Nonetheless, there is no evidence of fluctuation in the foreign exchange rate market, caused by changes in oil prices in Nigeria as at the time of the study since the shock effect between oil price and exchange rate dynamics is relatively not significant in the long run and hence, in explaining the reasons for volatility in exchange rate as represented in EGARCH result. Also, we observed a positive relationship between oil price, exchange rate dynamic and economic performance (proxy; real GDP). From the empirical findings, this study therefore recommends that government should reduce the pressure on exchange rate by diversifying the economy so as to reduce the pressure on oil. This will help to stabilize oil price and promote growth. Keywords: Oil price oscillation, Exchange Rate Dynamic, economic performance JEL Classifications: F30, F31, P33 DOI: https://doi.org/10.32479/ijeep.5944